Biomass and productivity in Mexican arid lands - Briones, Oscar; Búrquez, Alberto; Martínez-Yrízar, Angelina; Pavón, Numa; Perroni, Yareni (Instituto de Ecología, A.C., 2018)
Arid lands cover 54% of Mexico where over 40% of the total population inhabit these areas. Studies on the ecosystem functioning of the Mexican arid lands are still very limited. These studies have shown that mean aboveground biomass (23.2 Mg ha-1 ± 4.15, 23 sites) and belowground biomass (11.2 Mg ha-1 ± 3.54 Mg ha-1, 7 sites) were higher than those of the deserts of the world and their higher values were within the range for tropical deciduous forests (TDF). Net primary productivity in the driest regions of Mexico (< 0.5 Mg ha-1 y-1 - 3.4 Mg ha-1 y-1) was similar to the mean of the deserts of the world, but in the less dry regions it was almost four times larger and similar to the drier TDF. Total litterfall (2.85 Mg ha-1 y-1 ± 0.64 Mg ha-1 y-1, 12 sites) was higher than in the North American deserts and close to the lower end of values for TDF´s. Litter decomposition rate (0.001 g C y-1 - 4 g C y-1) was lower than in non-desert regions. Microbial respiration of soil (28.4 µg C g-1 d-1 ± 5.44 µg C g-1 d-1, 10 sites) depended mainly on precipitation and the concentration of carbon and nitrogen. Water availability is the main factor controlling biomass and productivity in the arid lands of Mexico. Since the sensitivity/resilience to land use change and other persistent global change pressures is still uncertain, more research on the dynamics of arid ecosystems is urgently needed.